The Role of Impulsivity in Post-Purchase Consumer Regret - Katarina Sokić; uro Horvat; Sanja Gutić Martinčić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Post-purchase consumer regret includes outcome regret and process regret. The aim of present study was to examine relationships between consumer regret, as indexed by the Post-Purchase Consumer Regret Scale (PPCR scale), attentional, motor and non-planning impulsivity, as measured by the Barratt Impulsiveness Scale (BIS-11), and Emotionality dimension of personality, as assessed by the HEXACO-60, in 211 undergraduates (96 men). Results partially supported hypotheses: motor and nonplanning impulsivity were associated with outcome regret, and attentional impulsivity was related to outcome and process regret. Contrary to the hypothesis, emotionality was not related to process regret. Additionally, these findings suggested that attentional impulsivity moderated the relationship between emotionality and outcome regret and that motor impulsivity moderated emotionality-process regret relationship.
Keywords: Z1; A12; 330; consumer regret; attention; motor; non-planning impulsivity; emotionality